Preparation and characterization of diltiazem nanocapsules: Influence of various polymers - Kumar, G Ashwini; Bhat, Amit; Rani, Shoba (Asian Journal of Pharmaceutics (AJP), 2014)
Nanocapsules are submicroscopic colloidal drug delivery system and are composed of an oily or an aqueous core surrounded by a thin polymeric membrane. Nanocapsules have recently generated lot of interest in the area of controlled release with availability of biocompatible and biodegradable polymers. Nanocapsules of diltiazem were prepared with an objective of achieving controlled release of the drug in order to reduce the frequency of administration of drug, to obtain more uniform plasma concentration, and to improve patient compliance. Diltiazem was chosen as the model drug, as it is widely used in the treatment of chronic conditions such as hypertension and angina which require prolonged therapy. Nanocapsules were prepared by the interfacial deposition technique by taking different concentrations of polymers and phospholipid mixture. Five best formulations were selected based on the encapsulation efficiency. The morphology of nanocapsules was assessed by scanning electron microscope and they were found to be smooth, spherical, and discrete. The particles followed normal size distribution with particle size in the range of 20 to 380 nm. In vitro release studies indicated prolonged release for all polymers for 48 hours, with polycaprolactone as the best polymer releasing about 95 to 98%.The formulations were stable at 4Â°C but unstable at 25Â°C, and hence recommended for storage in refrigeration.Thus, it can be concluded that nanocapsules are a useful technology for controlled release of diltiazem.